Strategies In The Procurement Of Sustainable Goods And Services In Green Infrastructure Development In North Gorontalo Regency - Akili, Ardiansyah S; Rahim, Sukirman; Tolinggi, Wawan K; Hamidun, Marini Susanti (Citakonsultindo, 2026)
Sustainable procurement of goods and services is increasingly relevant in relation to green infrastructure development. The 2025-2029 National Medium-Term Development Plan emphasizes green and blue architecture development as a step towards Net Zero Emission by 2060. The Regional Medium-Term Development Plan in North Gorontalo Regency has only recently been approved and has not yet been properly integrated. Therefore, an analysis is needed to examine internal and external factors as a form of determining strategies in sustainable procurement of goods and services in North Gorontalo Regency. This study uses a mixed method, combining qualitative and quantitative approaches. The analysis tool used is SWOT to identify internal and external factors and determine the most effective strategy to use in sustainable procurement of goods and services. The findings of this study are coordinates (0.28: 0.07) located in quadrant one, meaning that the most suitable strategy to use is a progressive strategy, namely by utilizing the strengths of sustainable goods and services procurement policies and existing opportunities. There are two strategies that can be implemented, namely: 1) Utilizing the strengths of regulations and the e-procurement system to accelerate the implementation of sustainable procurement. 2) Integrating the commitment of the North Gorontalo Regency Government with opportunities for national and international program support to strengthen the market for local environmentally friendly products.